2015
DOI: 10.4315/0362-028x.jfp-14-329
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection of Lactobacillus kefiranofaciens in Kefir Grain and Kefir Milk Using Newly Developed Real-Time PCR

Abstract: Lactobacillus kefiranofaciens is an indicator microorganism for kefir and a key factor in kefir grain formation and kefiran production. We designed a novel real-time PCR primer and probe set, LKF_KU504, for the rapid detection of L. kefiranofaciens. In inclusivity and exclusivity tests, only 14 L. kefiranofaciens strains were positive among 61 microorganisms, indicating 100 % sensitivity and specificity. The LKF_KU504 set also differentiated kefir milk from 30 commercial nonkefir yogurts. The levels of L. kefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…The average level of background microflora of the 82 beef samples was 4.53±2.67 log CFU per gram, suggesting that the real-time PCR assay could detect the targeted organism even when it was hidden by other background organisms in the culture media. The same phenomenon was observed in the real-time PCR assays for the detection of Listeria monocytogenes and Lactobacillus kefiranofaciens in food samples with high levels of background microflora (10,19). In addition, the results of the real-time PCR assay for detection of C. perfringens could be obtained within 30 h, whereas the conventional culture method requires 96 h (Fig.…”
Section: Resultssupporting
confidence: 66%
“…The average level of background microflora of the 82 beef samples was 4.53±2.67 log CFU per gram, suggesting that the real-time PCR assay could detect the targeted organism even when it was hidden by other background organisms in the culture media. The same phenomenon was observed in the real-time PCR assays for the detection of Listeria monocytogenes and Lactobacillus kefiranofaciens in food samples with high levels of background microflora (10,19). In addition, the results of the real-time PCR assay for detection of C. perfringens could be obtained within 30 h, whereas the conventional culture method requires 96 h (Fig.…”
Section: Resultssupporting
confidence: 66%
“…L. kefiri and L. kefiranofaciens have been recognised as indicator microorganisms of kefir and reported to have pivotal roles in the beneficial health effects of kefir (CODEX Alimentarius Commission 2003; Chen et al 2012; Kim et al 2015c, 2016). It is interesting that culture supernatnant of L. kefiri exerted stronger inhibition on C. sakazakii than that of L. kefiranofaciens , although the supernatnant of L. kefiranofaciens has lower pH and higher titrable acidity than that of L. kefiri .…”
Section: Resultsmentioning
confidence: 99%
“…Although not yet confirmed in vivo, several strains isolated from kefir have been shown to adhere to human enterocyte-like Caco-2 cells, indicating a potential ability to colonise the human gut [50]. Kefir, or its constituent strains, have also been shown to have a considerable impact on the gut microbiota population with increases in Lactobacillus , Lactococcus and Bifidobacterium concentrations, and reductions in Proteobacteria and Enterobacteriaceae concentrations, being demonstrated in numerous animal studies [51,52,53]. Furthermore, one study found higher concentrations of Firmicutes , Bacteroidetes and Prevotella , as well as a higher stool weight and stool water, in mice administered Lactobacillus kefiranofaciens (but not kefir per se ), a common strain found in kefir grains, compared to control [52].…”
Section: Kefirmentioning
confidence: 99%